(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: It is important to study cellular circulation of L-FABP-associated fatty acids (FA) and their oxidation through the classical pathway with activation of the PPARγ gene and under conditions of impaired lipid metabolism. Purpose: To investigate the pathogenetic mechanisms of diabetic retinopathy (DR) progression in type 2 diabetes mellitus (T2DM) patients differing in the PPARγ genotype. Material and Methods: This study involved 101 T2DM patients (101 eyes) with different stages of diabetic retinopathy (DR) as assessed by the ETDRS scale and 40 non-diabetics (controls) who were comparable in age, gender and body mass index. The polymorphism was detected by real-time PCR on a Real-Time Gene Amp® PCR System 7500 (Applied Biosystems). ELISA was used to determine serum L-FABP levels with Human L-FABP ELISA kit (Hycult Biotech). Results: Our findings allowed for developing a concept of differences in pathogenetic mechanisms of DR progression between patients differing in the PPARγ genotype. Among carriers of the wild-type PPARγ genotype, DR as a complication of diabetes develops as a result of chronic inflammation and through PPARγ-dependent gene transcription, expression of the enzymes that oxidize arachidonic acid, and synthesis of the metabolites affecting the endothelium, platelets, the blood clotting system, etc. In diabetic PPARγ polymorphism carriers, PPARγ-dependent gene transcription is inhibited, and fatty acids are utilized in the cell via other L-FABP mechanisms, which results in activation of direct peroxisomal oxidation and increased oxidative stress-induced inflammation. A new insight into differences in pathogenetic mechanisms of DR progression between T2DM patients differing in the PPARγ genotype provides the basis for subsequent clinical development of advanced, customized management schemes for patients with different DR stages to prevent further retinal damage.